GOOD CORPORATE GOVERNANCE PRACTICES AND SERVICE QUALITY IN ACEH HOSPITALS - Azanna Fasalli (GREET, 2024)
This study investigates the influence of Good Corporate Governance (GCG) on healthcare service quality in Aceh hospitals, Indonesia. Employing a mixed-methods design, data were collected from ten hospitals through surveys, interviews, and document analysis, enabling both quantitative validation and qualitative insights. Results reveal that hospitals with strong governance frameworks—characterized by transparency, accountability, and stakeholder engagement—achieve superior patient satisfaction and operational performance. Quantitative findings indicate a 30% increase in patient satisfaction and a 40% reduction in grievances, while qualitative evidence highlights improved staff morale and patient trust. However, governance implementation remains inconsistent, particularly in rural hospitals facing resource constraints and weak policy enforcement. Theoretically, this study contributes to governance and healthcare literature by examining the governance–quality nexus in a developing context. Practically, it offers policy and managerial recommendations, emphasizing training, regulatory incentives, and patient feedback systems as strategies to enhance hospital governance. Strengthening GCG is essential for building sustainable, equitable, and high-quality healthcare systems in Aceh and comparable settings.